2012
DOI: 10.1292/jvms.11-0511
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Pentosan Polysulfate Sodium on MAP-Kinase Pathway and NF-κB Nuclear Translocation in Canine Chondrocytes <i>In Vitro</i>

Abstract: ABSTRACT. Pentosan polysulfate sodium (PPS) has a heparin-like structure and is purificated from the plant of European beech wood. PPS has been used for the treatment of interstitial cystitis for human patients. Recent years, it was newly recognised that PPS reduce pain and inflammation of OA. The molecular biological mechanism of PPS to express its clinical effects is not fully understood. The purpose of the present study is to investigate a mechanism of action of PPS on inflammatory reaction of chondrocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 22 publications
3
28
0
1
Order By: Relevance
“…However, NFkB activation which is essential for iNOS induction and p38 lie on two distinct pathways that seem to be independently required for IL-1-induced iNOS expression [9,10]. While our laboratory previously demonstrated the inhibitory effects of PPS on the two pathways [30], by ICC, the present study confirms that indeed PPS impairs IL-1-induced NFkB p65 nuclear translocation but most interestingly we demonstrate that PPS colocalizes with NFkB p65. Therefore, the observed inhibition of IL-1-induced iNOS mRNA upregulation and rcIL-1β + TNF-α + LPS-induced iNOS protein expression by PPS is consistent with the inhibition of the NFkB pathway.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…However, NFkB activation which is essential for iNOS induction and p38 lie on two distinct pathways that seem to be independently required for IL-1-induced iNOS expression [9,10]. While our laboratory previously demonstrated the inhibitory effects of PPS on the two pathways [30], by ICC, the present study confirms that indeed PPS impairs IL-1-induced NFkB p65 nuclear translocation but most interestingly we demonstrate that PPS colocalizes with NFkB p65. Therefore, the observed inhibition of IL-1-induced iNOS mRNA upregulation and rcIL-1β + TNF-α + LPS-induced iNOS protein expression by PPS is consistent with the inhibition of the NFkB pathway.…”
Section: Discussionsupporting
confidence: 78%
“…PPS [30,3840] and other active glycosaminoglycans (GaGs) [41,42] have been proposed to exert their action through interaction with transcription factors and other intracellular proteins consequently blocking their downstream activity. ICC was performed to investigate colocalization of PPS with NFkB p65 and c-Jun, and to clarify whether PPS could inhibit NFkB p65 and c-Jun nuclear translocation and localization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[77][78][79][80] Pentosan polysulfate has been shown to mediate part of its antiinflammatory effects by downregulating TNF-a activity via the suppression of NF-Kb nuclear translocation and inhibition of the MAPKs pathways. 75,76,85 Since the levels of TNF-a 68 and ADAMTS-4/ADAMTS-5 51 are elevated in degenerative discs and have been implicated in the degradation of disc PGs, the combination of PPS with MPCs in the present study offered several potential advantages over the use of MPCs alone.…”
Section: Discussionmentioning
confidence: 98%
“…This interaction may be incorporated into the present model by including competitive interaction between IL-1α and anakinra for the IL-1 receptor. Similarly it has been shown that PPS may exert its principal protective action in cartilage by inhibiting the activity of proteases (aggrecanases and MMPs) and not by binding to IL-1α directly [97, 103]. In this case, the model can be modified to incorporate the PPS dependent activity of aggrecanases and MMPs.…”
Section: Discussionmentioning
confidence: 99%